Gestão por indicadores da estratégia corporativa: um estudo de caso - Colombo, Leandro Augusto (Universidade do Vale do Rio dos Sinos, 2011)
It is the fact that today organizations are in high market competition, hence the importance in the matter of choosing the most reliable gauges to achieve its strategy. Among the functional strategies, corporate and competitive, the latter has a scope in the scope of the main organization. Therefore the analysis of indicators in this light of the strategy will be the purpose of this study cervical. With the proliferation of competitive advantage based on quality, delivery, reliability, flexibility, cost and innovation, these increasingly widespread and worked by companies from the perspective of continuous improvement. However only the polishing of these strategies or group of them is a guarantee for success of continued growth. The company needs to know which strategy will have more advantage over pre-defined points, for the strategy to achieve its long-term goal. Soon to an effective analysis, the organization must have a system of indicators able to answer your strategy. Thus, this work is based initially with a theoretical exposition on the themes of strategy, corporate strategy, indicators and measurement systems. In the following will be discussed the methodology used in collecting and analyzing data, according to the actual examination of the data collected, compared with the suggestion in the literature. And finally the closing remarks on the subject, which is listing the author's suggestions, improvements to be made and opportunities for future work. This work aims to analyze the real situation of a case study in its management process from the conceptual character of the literature relevant topics.
Keywords: Estratégia; Estratégia corporativa; Indicadores; Medição de desempenho; Análise organizacional; Strategy; Corporate strategy; Indicators; Performance measurement; Organizational analysis